Application of Differentiated Learning Through the Use of Interactive Multimedia to Promote Students' Scientific Literacy - Sandra, Revielni; Asrizal; Werina, Werina (Universitas Negeri Padang, 2024)
Scientific literacy skills are an ability needed to face the 21st century. Scientific literacy is defined as the ability to know, complete, convey and apply science in everyday life. Scientific literacy skills make it easy for students to solve issues that occur in real life using scientific methods. The aim of this research is to improve students' scientific literacy skills by utilizing differentiated learning using interactive multimedia. The type of research carried out was classroom action research using the Kemmis and McTaggart model which was carried out in two cycles. Classroom action research consists of 4 stages, namely planning, implementation, observation and reflection. The research was conducted in the research subjects were students in class X.E.1 at SMA Negeri 3 Padang, totaling 36 students. The research results show that there is an increase in students' scientific literacy skills by implementing differentiated learning using interactive multimedia. The application of differentiated learning lies in the content and products presented using interactive multimedia which are based on students' learning readiness and interests.